Annual Editions : Management - Maidment,. Fred H. (McGraw-Hill, New York, 2009)
This Fifteenth Edition of ANNUAL EDITIONS: MANAGEMENT provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; and an online instructor$1 (Bs resource guide with testing materials. USING ANNUAL EDITIONS IN THE CLASSROOM is offered as a practical s
Keywords: Management